2004
DOI: 10.1139/y04-104
|View full text |Cite
|
Sign up to set email alerts
|

Digastric muscle activities in anoxic infant rats

Abstract: The digastric muscle acts for both feeding (including mastication and swallowing) and respiration. In this study, we examined whether or not the muscle activity is detectable during anoxia in developing rats. Rats at 4 different ages, days 5, 10, 16, and 24, were exposed to 100% N2 under pentobarbital or ketamine-xylazine anesthesia, and the electromyograms of digastric muscles (dEMG) and the diaphragm (diaEMG) were examined simultaneously. Prior to the anoxic exposure, at all ages, the dEMG was similar to or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It is possible that in the in situ decerebrated preparation the pathway that exists allowing the MhN to be incorporated into events that require synchronization with inspiratory breathing, such as gasping and hypoxia, is being utilized to transmit this signal in the absence of cortical control. However, it has been reported previously that neonatal and juvenile rats present inspiratory‐related activity in digastric muscle during basal breathing (Saiki & Matsumoto, ), suggesting that the observed pre‐I and inspiratory modulation of MhN in normocapnia is an essential component of the respiratory control of oropharyngeal resistance, at least in juvenile rats.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…It is possible that in the in situ decerebrated preparation the pathway that exists allowing the MhN to be incorporated into events that require synchronization with inspiratory breathing, such as gasping and hypoxia, is being utilized to transmit this signal in the absence of cortical control. However, it has been reported previously that neonatal and juvenile rats present inspiratory‐related activity in digastric muscle during basal breathing (Saiki & Matsumoto, ), suggesting that the observed pre‐I and inspiratory modulation of MhN in normocapnia is an essential component of the respiratory control of oropharyngeal resistance, at least in juvenile rats.…”
Section: Discussionmentioning
confidence: 81%
“…The same is true for the glottal control of laryngeal airway resistance during pre‐I and inspiratory phases (Paton & Dutschmann, ; Richter & Smith, ). On the other hand, oral breathing associated with jaw movements is presumed to be a transient behaviour that appears during airway obstruction or high chemical drive (Carlo et al., ; Saiki & Matsumoto, ). In this regards, previous studies reported inspiratory‐related activity in jaw‐opening submandibular muscles (including digastric) during asphyxia and apnoea (Carlo et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of ala nasi muscles results in a decrease in nasal and total respiratory resistance (Mathew, 1984). The platysma and digastric muscles show respiratory‐modulated activity under high respiratory drive (De et al 1986; Saiki & Matsumoto, 2004), the mentalis muscle under quiet breathing (Dutra et al 2006). Thus, we surmise that the brainstem of newborn mice already has in place the pattern forming circuits that are necessary to activate the parts of the facial nucleus needed to maintain airway patency.…”
Section: Discussionmentioning
confidence: 99%